Urban dynamics and urban sprawl in hill stations of India: a case study of Shillong city - Kharpran, F Phibawanlang; Purkayastha, Subrata (Acta Geographica Debrecina Landscape & Environment series, 2024)
The hill stations of India are remnants of colonial past built by the British where the scenic landscape and climate similar to Britain attracted the British to set up cantonments and sanatoriums for the British troops and their families. Shillong City whose origin dates back to the 19th century, was the British capital of Assam Province, the administrative seat of undivided Assam after India’s Independence and at present the capital of Meghalaya. The city’s growth resulted from the continuous influx of population to fulfil the changing socio-economic and political dynamics of the city.  This hill station was built by the British with a vision to house a population of less than one lakh. It was then a cluster of a few scattered hamlets, which at present has grown tremendously with 12 contiguous urban units forming the Shillong Urban Agglomeration (SUA). With the help of RS -GIS using Shannon entropy technique as a landscape metric, the urban sprawl of Shillong has been measured from the year 1991 to 2001.The rapid growth has led to an urban sprawl which poses various challenges to the city’s environment.